2007
DOI: 10.2353/ajpath.2007.060651
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor γ Contributes to the Survival of T Lymphoma Cells by Affecting Cellular Metabolism

Abstract: Peroxisome proliferator-activated receptor gamma (PPARgamma) is a metabolic regulator involved in maintaining glucose and fatty acid homeostasis. Besides its metabolic functions, the receptor has also been implicated in tumorigenesis. Ligands of PPARgamma induce apoptosis in several types of tumor cells, leading to the proposal that these ligands may be used as antineoplastic agents. However, apoptosis induction requires high doses of ligands, suggesting the effect may not be receptor-dependent. In this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…36 PPAR␥, a ligand-activated transcription factor belonging to the nuclear receptor superfamily, regulates gene expression of key proteins involved in lipid metabolism, vascular inflammation, and proliferation, providing protection against atherosclerosis and coronary events. 37 Recently, Yang et al 38 have demonstrated that PPAR␥ activation lowers the ROS levels through coordinated transcriptional control of a set of proteins and enzymes involved in ROS metabolism. PPAR␥ increases the amount of uncoupling protein 2 and superoxide dismutase and reduces the amount of the p67 subunit of NADPH oxidase at both the mRNA and protein levels in T lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…36 PPAR␥, a ligand-activated transcription factor belonging to the nuclear receptor superfamily, regulates gene expression of key proteins involved in lipid metabolism, vascular inflammation, and proliferation, providing protection against atherosclerosis and coronary events. 37 Recently, Yang et al 38 have demonstrated that PPAR␥ activation lowers the ROS levels through coordinated transcriptional control of a set of proteins and enzymes involved in ROS metabolism. PPAR␥ increases the amount of uncoupling protein 2 and superoxide dismutase and reduces the amount of the p67 subunit of NADPH oxidase at both the mRNA and protein levels in T lymphoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of cell viability, cells were stained with 2 μg/mL propidium iodide (Molecular Probe), as described previously (21,22). Ten thousand events in a live cell gate were counted by a FACS Calibur (BD Biosciences).…”
Section: Translational Relevancementioning
confidence: 99%
“…Intracellular reactive oxygen species were detected with 5-(and 6-)carboxy-2′,7′-dichlorodihydrofluorescein diacetate (DCF; Molecular Probes), as described previously (21,22). Aliquots of 3 × 10 5 cells were resuspended in 500 μL of RPMI 1640 containing 5% FBS and loaded with 10 μmol/L DCF for 30 min at 37°C.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, rosiglitazone was found to protect lymphoma cells from serum starvation-induced apoptosis. 22 A low dose of rosiglitazone was found to stimulate the growth of estrogen receptor-positive breast cancer cells, whereas a high dose of rosiglitazone inhibits their proliferation. 23 Furthermore, the effect of rosiglitazone on cancer cells can be either PPARg-dependent or independent, despite it being a potent and highly selective agonist for PPARg.…”
mentioning
confidence: 99%